Efeito de uma intervenção cognitivo-comportamental nos aspectos psicológicos, clínicos e neuroendócrinos em pessoas com psoríase em placas - Silva, Leonardo Machado da (2013)
Psoriasis is a dermatological condition that has an interface with primary and secondary aspects of psychology. The primary interface aspects are those linked to stress as a precipitator or as an exacerbating factor on psoriatic lesions. Secondary aspects are related to illnesses/symptoms arising from psoriatic conditions, such as depression, social burden, suicidal ideation, feelings of shame and humiliation, anxiety and discrimination from others. However, very few treatments to psoriasis take into account psychological tools to help tackling the disease and its consequences. This study proposes a novel individual cognitive-behavior therapy-based intervention to assess its effect on psychological, clinical and neuroendocrine aspects in patients with plaque psoriasis. The secondary objectives include to identify the influence of the proposed intervention on stress levels, patient´s quality of life and anxiety and depression symptoms, as well as its possible effects on psoriatic lesions. First session of this thesis involved a systematic review of literature, aiming at searching for published educational and psychological interventions targeting psoriasis, in the previous twenty years. After a computerized search on PubMed/Medline, PsycInfo (APA), ProQuest and Pepsic databases, thirty-six articles were selected for analysis, from which only seven (n=7) constituted the final sample. The results revealed one educative intervention, two involving psychological interventions only and four studies were symptom-management multi-disciplinary programs. Although there had been an increasing number of interventions in the last years, it was concluded that a larger number and more robust studies are necessary to fulfill the clear demand for psychological interventions to help treating psoriasis. The next two sessions report empirical studies with the same methodology. Patients with plaque psoriasis (N=44) were submitted to a 10-session cognitive-behavioral based individual intervention and assessed at baseline and postintervention for the following variables: clinical severity of the disease (PASI Psoriasis Area and Severity Scale), stress levels (ISSL Inventory), depression (BDI-II) and anxiety levels (BAI), and quality of life (SF-36). Salivary cortisol was obtained in order to assess the performance of the hypothalamic-pituitary-adrenal axis. The second session was a brief communication showing the preliminary data of the study. Eighteen patients were divided into two groups: intervention only (IO) (n=11) and adjunct treatment (AT) group (n=7). Results showed a significant reduction on PASI scores, depression and anxiety levels, as well as an improvement on two domains of quality of life. Cortisol levels, however, did not show significant changes over time in any of the four measures. Third session comprised of the final results of this study, where thirty patients (n=30) were divided into two groups, IO (n=16) and AT (n=14). Results confirmed the preliminary scores on PASI reduction (p=0,031), depression (p<0,001) and anxiety (p=0,001) levels, as well as the improvement on two domains of quality of life: bodily pain (p=0,033), social role functioning (p=0,003) and mental health (p=0,003). Salivary cortisol, however, was lower in three takes, morning and (p=0,030) afternoon (p=0,041) levels, and on the daily pattern (p=0,039). The results showed improved outcomes of the intervention in all types of variables, clinical, biological and psychological measures. This study demonstrated effective results on clinical outcomes for patients with plaque psoriasis, and helps to increase evidence on the importance of including psychosocial variables in any studies involving treatment of psoriasis.